Efforts to Protect the Law of Sexual Violence Cases Against Children Relate to Law Number 35 of 2014 Concerning Child Protection - Gagarin, M.Gary; Dewi, Sartika; Asyhadi, Farhan; Amaliya, Lia; Arafat, Zarisnov (Ridwan Institute, 2024)
The Integrated Service Center for the Empowerment of Women and Children (P2TP2A) is expected to function as a community-based service institution. This community-based service acts as a crisis center unit by providing complaints, health, rehabilitation, social, counseling, legal assistance, repatriation, and social reintegration services (for trafficking victims). Sexual violence encompasses any action that diminishes, belittles, intimidates, or assaults an individual's body or reproductive capabilities, stemming from imbalanced power dynamics or gender inequalities. Such acts inflict psychological or physical harm, potentially disrupting reproductive health and impeding educational opportunities. Examples include rape and sexual abuse. This research focuses on examining legal protection efforts and identifying obstacles faced by P2TP2A (Integrated Service Center for Women and Children) in handling cases of sexual violence against children, utilizing an empirical juridical approach. The findings reveal that legal protection for children experiencing sexual violence is enshrined in Article 13 of Law Number 35 of 2014, which emphasizes the rights of children to be protected from various forms of harm, including discrimination, exploitation, neglect, cruelty, violence, abuse, and injustice. Supporting factors include the availability of financial assistance to fund P2TP2A activities, the dedication of officers and volunteers who prioritize the welfare of women and children, and the provision of office facilities by the government. However, there are inhibiting factors such as inadequate budget allocation, the unrealized Community-Free Integrated Child Protection Program (PATBN), insufficient human resources, the need for improvement in office facilities and infrastructure, and the lack of safe housing for victims who are still renting.